O REAL E O IMAGINÁRIO NA IMAGEM DA TELENOVELA BRASILEIRA EXPORTADA - Yamauti, Amauri (2005)
The telenovela developed itself along historical facts of the Brazilian society. As the telenovela became a space to portray the characteristics of a people who searchs an identity, the telenovela itself helped to construct this national identity. Through a bibliographical study we aim a speech about the image produced in the telenovela and re-elaborated by the spectator, infering on the acceptance of telenovela in other countries, once it is a specific product developed by and for the brazilian society. The conclusions point to a relation, stablished on the emotional and symbolic plan, between image and spectator, beeing a device for recognition and motivator.